Design and analysis of a low-carbon lignite/biomass-to-jet fuel demonstration project. (15th February 2020) - Larson, Eric D.; Kreutz, Thomas G.; Greig, Chris; Williams, Robert H.; Rooney, Tim; Gray, Edward; Elsido, Cristina; Martelli, Emanuele; Meerman, Johannes C.
Highlights: Detailed prefeasibility design study for jet fuel made from lignite and woody biomass. First-of-a-kind demonstration plant (1252 barrels per day) is technically viable. 25% biomass input fraction gives jet-fuel with near-zero net carbon emissions. High capital and operating costs result in poor economics, in absence of a subsidy. Abstract: Biomass-derived synthetic jet fuel with low net greenhouse gas emissions can help decarbonize aviation. Demonstration projects are required to show technical feasibility and give confidence to investors in large commercial-scale deployments. Most previous literature focuses on assessing future commercial-scale systems, for which performance and costs will differ considerably from demonstration projects. Here, a detailed analysis is presented for a first-of-a-kind demonstration plant that would be built in the Southeastern US. The plant, which cogasifies biomass and lignite and captures CO2 prior to Fischer-Tropsch synthesis, was designed and simulated using Aspen Plus. The process heat recovery system was designed using a systematic optimization method. Lifecycle analysis was used to assess net greenhouse gas emissions. Capital and operating cost estimates were developed in collaboration with a major engineering firm. The plant produces 1252 barrels per day (80% jet fuel), exports 15 MWe (net), and has a net energy efficiency of 35.8% (lower heating value). Captured CO2 (1326 t/d) is sold for use in enhanced oil recovery. With biomass coming from sustainably-managed pine plantations, net lifecycle greenhouse gas emissions are well below those for petroleum jet fuel. The estimated range of capital required to build the plant is 3875–5762 $/kWth of feedstock input (2015$). As expected for a small demonstration designed to minimize technological risks, subsidies are required for the jet fuel product to compete with petroleum jet fuel. Technology innovations, learning via construction and operating experience, and larger plant scales will improve the economics of future commercial plants.